What are the Determinants Affecting the Financing Risk in Indonesian Sharia Rural Banks? - Suhel Suhel; Abdul Bashir; Imam Asngari; Ichsan Hamidi (IAIN Salatiga, 2022)
Rapid and dynamic changes in the financial and economic systems are posing various risks and instabilities to Islamic banking institutions. Therefore, this study aims to investigate the impact of macroeconomic factors and bank abilities on financing risk in Indonesia. In this analysis, the 2005-2019 sharia banking statistics at 92 rural banks were emphasized in the country. A panel data regression was also employed with the fixed effect method during the experimental procedure. The results showed a negative and significant relationship between economic growth, FDR (financing to deposit ratio), and CAR (capital adequacy ratio) toward financing risk. Moreover, a positive and significant relationship was found between the benchmark loan rate on financing risk, although inflation had no significant effect. Economic growth was also a key factor influencing financing risk in the sharia rural banks sector. Based on these results, banking regulators were found to operate according to sharia principles, to selectively optimize and carefully monitor financial distribution and activities with high financing risk.